Hydraulic conductivity in stem of young plants of Jatropha curcas L. cultivated under irrigated or water deficit conditions - de Oliveira, Priscila Souza; Pereira, Lidiane Silva; Silva, Delmira Costa; de Souza Júnior, José Olimpio; Laviola, Bruno Galvêas; Gomes, Fábio Pinto (Industrial crops and products, 2018)
•Stem hydraulic conductivity was variable among ten genotypes of Jatropha curcas.•Stem hydraulics was not related to leaf gas exchange across all the genotypes.•Drought-induced changes on anatomy of stem xylem and on root growth.•Plasticity of hydraulic and anatomical traits under drought is genotype dependent. Jatropha curcas L. can survive situations of water deficiency, in which carbon assimilation and growth rates are severely affected, which can ultimately result in low productivity. With the objective of evaluating the hydraulic conductivity of stem xylem and its relationship with leaf gas exchange under water deficiency, two-month old plants of ten genotypes of J. curcas from an improved population were cultivated under water restriction (soil water content of 14%) or under full irrigation (soil water content of 22%) for 60 days. Water deficit led to significant increase of leaf area-specific hydraulic conductivity (LSCn) in genotype CNPAE 517 and decrease in CNPAE 556, 557, 559, 569 and 570. Of those five genotypes, only in CNPAE 556 there was no decrease of leaf water potential measured around 4 h. Genotypes CNPAE 516, 517 and 520 can be highlighted, where elevated rate of net photosynthesis were observed even under water restriction. Changes in the anatomy of the xylem vessels, as well as in root biomass when submitted to water deficiency favored a greater or lesser drought tolerance of the genotypes when the native or potential hydraulic conductivity were analyzed. In summary, high plasticity for hydraulic and anatomical traits, as observed for the genotypes CNPAE 516, 517 and 520 must be considered for further investigation on the tradeoffs between hydraulic conductivity and productivity, in the search for genetic material suitable for cultivation in areas subject to short periods of soil water deficit.